Arvottavien merkitysten rakentaminen taloussanomalehtien pääkirjoituksissa - Katajamäki, Heli (Vaasan yliopisto, 2006)
This article focuses on the subjectivity of evaluation in the language use in the Finnish business newspaper, Taloussanomat. The aim is to discuss the linguistic features which are explicitly evaluative, either positively or negatively. Furthermore, I will discuss how evaluation is construed in texts. The considerations are based on empirical evidence of chosen linguistic features used in 19 editorials of Kauppalehti and Taloussanomat published in September 2001 and 2005. The theoretical basis of the study is Appraisal theory, which shares the systemic-functional view of language (eg. Martin 2000). According to the appraisal theory, language is approached from the interpersonal perspective and from the point of view of Attitude, which is a part of Appraisal system concentrated in semantic resources "used to negotiate emotions, judgements, and valuations" (2000: 145). The Appraisal system is divided in to Affect, Judgement and Appreciation. The preliminary results imply that Appreciation is the most commn way to evaluate in the editorials and Affect and Judgement are less common. If Affect is used, it is reificated by using grammatical metaphors. The axes of the mostly used explicit evaluations are threat and possibility, weakness and strength, difficult and easy, bad and good, evil and good, suspicious and countable, unsuccess and success, fear and fearless and grief and happy.
Keywords: subjektiivisuus; arvottava kielenkäyttö; taloussanomalehti; pääkirjoitukset; tekstintutkimus; fi=Viestintätieteet|en=Communication Studies|